Gambaran Tingkat Stress Penderita Lupus Eritematosus Sistemik - Rahayu, Dinda Sinta; Udijono, Ari; Saraswati, Lintang Dian; Mertini, Martini (Jurnal Ilmiah Mahasiswa, 2021)
Systemic Lupus Erythematosus (SLE) is a lifelong autoimmune disease with varied manifestations. Patients with SLE can have a certain impact because of the theraphy and the disease itself, both physically and psychologically, one of the psychologically impact is stress. The study aims to determine the description of stress levels in SLE patients who came to examine themselves at Central General Hospital in Semarang City. This study used a cross sectional study design. The sample size in this study were 136 respondents. The measuring tool used is a questionnaire of Depression Anxiety Stress Scale consisting of 14 questions. The results of the research that have been conducted show that most of the patient experience stress with normal level. Researchers provide suggestions for further researchers to use questionnaire of Depression Anxiety Stress Scale that have been modified in each questions.Â